2008
DOI: 10.1016/j.jtcvs.2008.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Surgical ablation for atrial fibrillation: The efficacy of a novel bipolar pen device in the cardioplegically arrested and beating heart

Abstract: Objective The introduction of ablation technology has simplified surgical intervention for atrial fibrillation. However, most ablation devices cannot create focal transmural lesions on the beating heart and have difficulty ablating specific regions of the atria, such as the atrioventricular isthmus, coronary sinus, and ganglionated plexus. The purpose of this study was to examine the efficacy of a pen-type bipolar radiofrequency ablation device on both arrested and beating hearts. Methods Endocardial and epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…In prior studies, ovine and porcine hearts were used to evaluate ablative lesions with bipolar RF energy; transmurality of lesions was achieved with atrial wall thicknesses as much as 5 mm [7,[9][10][11][12][13]. Of note, these hearts did not have hypertrophy of the atrial wall or atherosclerosis of the coronary arteries.…”
Section: Transmuralitymentioning
confidence: 99%
“…In prior studies, ovine and porcine hearts were used to evaluate ablative lesions with bipolar RF energy; transmurality of lesions was achieved with atrial wall thicknesses as much as 5 mm [7,[9][10][11][12][13]. Of note, these hearts did not have hypertrophy of the atrial wall or atherosclerosis of the coronary arteries.…”
Section: Transmuralitymentioning
confidence: 99%
“…In this case, a bipolar radiofrequency pen device was applied to ablate the accessory pathway. This device has been shown to create sufficient lesion depth on the beating heart with a stamping technique [6]. Irreversible disappearance of the delta wave suggested that the pen device achieved complete ablation of the accessory pathway.…”
Section: Commentmentioning
confidence: 99%
“…The ablation duration was set at 15 s in accordance with the acceptable ablation depth and width determined in a previous experimental study [7]. Ablation was repeated as many as three times until the vagal response was completely eliminated.…”
Section: Sequential Pacing and Ablation Techniquementioning
confidence: 99%